Oil yield components of maize crops exposed to heat stress during early and late grain-filling stages - Mayer, Luis Ignacio (2014)
Heat stress frequently limits grain yield of summer crops. Most research on maize (Zea mays, L.) has analyzed heat stress effects on crop physiology and kernel set, but little attention has been given to kernel weight and its composition. The objectives of this work were (i) to assess the response of maize oil yield components (kernel number and weight, embryo oil concentration and embryo/kernel ratio) to postflowering heat stress, and (ii) to explore changes in the sensitivity to this constraint across developmental stages and genotypes. Hybrids with different kernel type (flint, popcorn and semident) were exposed to contrasting temperature regimes (nonheatedand heated: air temperature at ear level>35ºC) during early or late stages of the effective grain filling. Oil yield was affected by early (up to -60%), and to a lesser extent, late (up to -40%) heat-stress episodes. These effects were mediated by lighter kernels (r2=0.94; P<0.001) and lower kernel oil concentrations (r2=0.80; P<0.001). Reductions of kernel weight were related to shorter grain-filling periods (r2=0.48; P<0.01), and those of kernel oil concentration were mainly associated with lower embryo oil concentrations (r2=0.64; P<0.001). Kernels of semident hybrids were the most prone to alter their weights and oil concentrations in the face of a wide range of heat stress intensities. Variations in kernel oil concentration due to high temperature became notorious when kernel weight reductions were larger than 20%.